2011
DOI: 10.1093/jac/dkq526
|View full text |Cite
|
Sign up to set email alerts
|

The third-generation P-glycoprotein inhibitor tariquidar may overcome bacterial multidrug resistance by increasing intracellular drug concentration

Abstract: We conclude that tariquidar has potent inhibitory effect against certain bacterial efflux pumps in vitro. Their high activity at clinically achievable concentrations might yield this class of drugs promising for future applications in infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…In particular, a concentrationdependent inhibition of P-gp function has been observed. Taking into account that Zuccagnia punctata extracts as mentioned in the introduction are endowed with antibacterial activity against antibiotic-resistant bacteria, and that the P-gp inhibitors may be able to overcome bacterial multidrug resistance (Leitner et al, 2011), the here observed inhibitory effects of Zuccagnia punctata extract and related polyphenols on P-gp activity in human cells, suggest a potential multidrug resistance reversal ability of these natural drugs that needs to be explored more in depth.…”
Section: Resultsmentioning
confidence: 81%
“…In particular, a concentrationdependent inhibition of P-gp function has been observed. Taking into account that Zuccagnia punctata extracts as mentioned in the introduction are endowed with antibacterial activity against antibiotic-resistant bacteria, and that the P-gp inhibitors may be able to overcome bacterial multidrug resistance (Leitner et al, 2011), the here observed inhibitory effects of Zuccagnia punctata extract and related polyphenols on P-gp activity in human cells, suggest a potential multidrug resistance reversal ability of these natural drugs that needs to be explored more in depth.…”
Section: Resultsmentioning
confidence: 81%
“…Several investigators are actively involved in the search for such inhibitors (14,19) to treat various bacterial infections. Recently, a third-generation P-glycoprotein inhibitor, tariquidar, has been reported to be a potent inhibitor of certain bacterial efflux pumps in vitro (17).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, however, similar findings could not be reproduced in phase II clinical trials [64,65]. Drugs like XR9576, OC 144-093, and valspodar have been used as inhibitors of the protein ATPbinding cassette (ABCB1), which involves in drug-resistance of certain tumours [66][67][68]. ABCB1 is a P-glycoprotein that is not expressed by many cell types [66].…”
Section: Discussionmentioning
confidence: 99%